...and someone cared enough about me in this world to take my picture - Ng, Teng Han (Nanyang Technological University, 2024)
...and someone cared enough about me in this world to take my picture is a curious attempt to reconnect with the younger self. The project makes use of archival photographs that represent memories of which the artist possesses but has close to no recollection of, revealing the fragility of memories while questioning its reality. Contemplating the “loss” of memory in our “infinite” memory storage, the detachment and disconnect is visually represented through physically manipulated photographs, which the selected method of manipulation seeks to underscore the distinctiveness of each recollected memory. As memories intertwine to construct their own distinct language, they become enigmatic and detached from any particular time or place, highlighting the malleability of perceptions on the memories that we hold dear to our heart.